English phonetics and phonology : an introduction - Carr, Philip, 1953- (Wiley-Blackwell, 2020)
"Thoroughly updated and with new and expanded chapters, the third edition of English Phonetics and Phonology remains an ideal introductory text to support students with no previous knowledge of articulatory phonetics as well as non-native speakers of English. Two new chapters have been added to this greatly popular textbook, to offer greater flexibility for teachers and increased support for non-native speakers studying the sound systems of English. The first new chapter is based on first-language acquisition, including the mental lexicon and the emergence of phonological rules and representations. The second additional chapter focuses on second-language acquisition of English phonetics and phonology, specifically including acquisition by French, German, and Japanese speakers"--